Detection of single nucleotide polymorphisms (SNPs) in HER2, MUC1, ESR1, and BRCA1 genes associated with canine mammary cancer - Carvajal-Agudelo, Juan D. (Array, 2021)
Worldwide, canine mammary cancer (CMC) is the most frequent type of neoplasia in female dogs, and it is three times more frequent in dogs than in humans. In Colombia, CMC is the second most frequent type of cancer, after skin neoplasia. Genetics is one of the most important factors in- volved in any type of cancer, and the genetic ba- sis of this disease is reflected through line breed- ing due to changes in allelic frequencies that are traceable using molecular markers. This study aimed to detect single nucleotide polymorphisms (SNPs) associated with CMC in blood samples collected from collected from healthy and CMC female dogs at Diego Villegas Toro Veterinary Hospital of Universidad de Caldas (Manizales, Colombia). We designed primers using Primer- BLAST and Primer3, and gene fragments from HER2, MUC1, ESR1, and BRCA1 were amplified to identify SNPs through genome mapping using the UCSC Genome Institute genome browser. We used the genome of Canis lupus familaris Boxer breed [GCF_000002285.3, (CanFam 3.1)] as a refer- ence to compare the gene fragments and SNPs. We associated SNPs with the CMC and control groups by testing odds ratios (OR) through Fish- er"s exact tests to determine an association or risk for CMC. We detected two SNPs for ESR1, three for MUC1, six for HER2, and one for BRCA1. MUC1 was the only gene to display an SNP in an exonic region that resulted in an amino acid substitution (Pro>Thr). No significant differences based on the OR were found, though the majority of SNPs, with the exception of four, were found in females with CMC. We report a novel molecu- lar marker for HER2 that amplifies exons 25–26 and introns 24–25, and highlight the importance of conducting further studies on MUC1 and elu- cidating the role of introns and splicing in candi- date genes associated with CMC.